Perkembangan Adaptasi Sosial Anak Usia Toddler dan Pola Asuh Orang Tua - Nur Syamsi Norma. L; Trimaya Cahya Mulat; Nur Srianingsihi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Every child has two developmental processes namely growth or evolution and setback or involution occurs simultaneously in human life. The purpose of this research is to find a picture of the development of a social adaptation of children aged toddler and parenting parents. The research design used is a descriptive method describing the state or status of the phenomenon. The population in this study were all mothers with children aged 1-3 years. The results show that the pattern of parenting for toddler age children in Barombong Kelurahan, Makassar City, most of the parents who have good parenting but there are still parents who have poor parenting. Conclusions increase knowledge about parenting and social adaptation abilities of children by finding as much information as possible through print media, or electronic media so that the development of toddler age social adaptation through parenting parents can develop properly.